Mesenteric lipoma: a rare cause of acute small bowel obstruction - Chatterjee, Debarghya; Raina, Vijay; Sharma, Rajeev (International Surgery Journal, 2021)
Lipomas, also known as universal tumors, can be found almost anywhere in the human body. However mesenteric lipomas are rare entities, with less than 100 cases reported in clinical literature. Patients may present with chronic non-specific abdominal symptoms, or rarely acute intestinal obstruction. Multiple imaging modalities are available for pre-operative diagnosis. Surgical intervention is required for treatment of symptomatic mesenteric lipomas.